2022
DOI: 10.1353/hpu.2022.0010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Mother-Infant Dyadic Video-Feedback Intervention in a Community Health Center in South Bronx, New York City

Abstract: Objective. This study evaluates a video-feedback program's effectiveness in promoting responsive and sensitive parenting for families in care in a community health center located in the South Bronx, New York City. Methods. Change in measures of parent responsiveness/ sensitivity (Global Rating Scale), depression (Patient Health Questionnaire 9), anxiety (Generalized Anxiety Disorder 7), and parenting stress (Parenting Stress Index-Short Form) were analyzed for mother-infant dyads (N=34) completing a six-sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…In this study, participants reported that participating in a video‐feedback program set in a community health center helped them become more sensitive and responsive parents. These perceptions are congruent with the findings of a quantitative evaluation of our program demonstrating significant improvements of 14% to 20% in measures of responsive and sensitive parenting by the end of the program 34 . Other studies, including several systematic reviews and meta‐analyses, have consistently shown that video‐feedback programs improve parental sensitivity 13,15,16 and child behaviors 12,13,15,16 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, participants reported that participating in a video‐feedback program set in a community health center helped them become more sensitive and responsive parents. These perceptions are congruent with the findings of a quantitative evaluation of our program demonstrating significant improvements of 14% to 20% in measures of responsive and sensitive parenting by the end of the program 34 . Other studies, including several systematic reviews and meta‐analyses, have consistently shown that video‐feedback programs improve parental sensitivity 13,15,16 and child behaviors 12,13,15,16 .…”
Section: Discussionsupporting
confidence: 86%
“…At entry to the program, a significant percentage of participants reported depressive symptoms sufficiently high enough on PHQ‐9 to be associated with clinical depression. Readers interested in a fuller description of the sample and a discussion of the quantitative outcomes of our program are referred to a recent publication on our program 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation